2010
DOI: 10.1071/py10024
|View full text |Cite
|
Sign up to set email alerts
|

Less germs, less mucus, less snot: teachers' and health workers' perceptions of the benefits and barriers of ear health programs in lower primary school classes

Abstract: This study explored health and education professionals' perceptions of the health benefits and barriers of different ear health programs used in lower primary school classes in two district education areas in the Goldfields South East Health Region, Western Australia. Health and education staff providing services to children in kindergarten to year three primary school classes were sent a questionnaire about ear health programs provided in their school. Sixty-one questionnaires were returned from 43 teachers, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 13 publications
0
16
0
Order By: Relevance
“…30,35,36,[46][47][48][51][52][53] As documented in the literature, studies consistently reported high levels (ranging from 42% to 64%) of OM among Indigenous children. 26,27,33,42,49 Some included studies reported increased OM knowledge and correct diagnosis resulted in improved child behaviour, 22,31,38,43 school performance, 22,38 family life 22,38 and physical health. 43 Three studies primarily focused on strengthening ear health screening skills and confidence for IHWs 9,15,51 and one study stressed the importance of providing specialised training for non-Indigenous Health Workers to generate a better understanding of Indigenous health contexts.…”
Section: Results Of Individual Sources Of Evidencementioning
confidence: 99%
See 4 more Smart Citations
“…30,35,36,[46][47][48][51][52][53] As documented in the literature, studies consistently reported high levels (ranging from 42% to 64%) of OM among Indigenous children. 26,27,33,42,49 Some included studies reported increased OM knowledge and correct diagnosis resulted in improved child behaviour, 22,31,38,43 school performance, 22,38 family life 22,38 and physical health. 43 Three studies primarily focused on strengthening ear health screening skills and confidence for IHWs 9,15,51 and one study stressed the importance of providing specialised training for non-Indigenous Health Workers to generate a better understanding of Indigenous health contexts.…”
Section: Results Of Individual Sources Of Evidencementioning
confidence: 99%
“…26,27,33,42,49 Some included studies reported increased OM knowledge and correct diagnosis resulted in improved child behaviour, 22,31,38,43 school performance, 22,38 family life 22,38 and physical health. 43 Three studies primarily focused on strengthening ear health screening skills and confidence for IHWs 9,15,51 and one study stressed the importance of providing specialised training for non-Indigenous Health Workers to generate a better understanding of Indigenous health contexts. 35 Challenges research teams faced in maintaining the success of their screening programs included the resource-intensive nature of programs, 30 high healthcare and teaching staff turnover, 35,40 limited OM knowledge in communities and schools, 39,40 service accessibility 35,39 and limited evaluation methods.…”
Section: Results Of Individual Sources Of Evidencementioning
confidence: 99%
See 3 more Smart Citations